Three new species of Idiops Perty, 1833 (Araneae: Idiopidae) from India - Gupta, Neha; Ganeshkumar, M.; Das, Sanjay Keshari; Siliwal, Manju (Zootaxa, 2013)
Three new species of the front-eyed trapdoor genus Idiops, viz., Idiops joida sp. nov. from the Western Ghats of Karnataka, I. mettupalayam sp. nov. from the foothills of the Western Ghats in Tamil Nadu and I. oriya sp. nov. from Odhisa, are described. Natural history information for all these species is provided as is an identification key to Idiops species from South andSoutheast Asia.